Strategy formulation and implementation for PT Bina Lestari Nusantara - Indahdewi, Lauditta; Inggriantara, Alibasjah (The Indonesian Journal of Business Administration, 2016)
Abstract - PT Bina Lestari Nusantara is a construction company that focused on telecommunication tower infrastructure established in 2008. PT BLN provide service for its client by provide coverage solutions and expand network capacity through build-to-suit developments. The company faced several obstacles such as inconsistent of revenue and experience slow growth. The company also have difficulties in terms of efficiency which resulted in low profitability. This condition shows that the existing company strategy is no longer to be able to overcome the company’s obstacle. PT BLN need a new proper strategy for solving their problems to give a positive effect in their financial performance. Formulating strategies start by analysing internal and external environments using PEST analysis, Porter’s five forces analysis, business model canvas, and financial analysis. This analysis will be summarized as SWOT analysis which continued to be interpreted on SWOT diagram for positioned the appropriate strategy. The result shows that company is in weak internal position. The company is suggested to applied defensive strategy. Defensive strategy will be solving the company’s problem who experience weak internal position. Defensive strategy continues to be interpreted in action plan and financial projection for the next three year. Three years is appropriate time of defensive strategy for taking off and going into the next strategy which is supporting aggressive. The company also need to applied focused differentiation, where company should seeks differentiation in a targeted market segment. The company need to revise all building blocks elements of business model canvas. Strategy formulation will help company to applied efficient work.Keywords: BTS tower company, financial analysis, SWOT Diagram, Generic Business Strategy